2021
DOI: 10.3390/su13147729
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Compressive Strength of Rubberized Concrete Using Artificial Intelligence Methods

Abstract: In this study, support vector machine (SVM) and Gaussian process regression (GPR) models were employed to analyse different rubbercrete compressive strength data collected from the literature. The compressive strength data at 28 days ranged from 4 to 65 MPa in reference to rubbercrete mixtures, where the fine aggregates (sand fraction) were substituted with rubber aggregates in a range from 0% to 100% of the volume. It was observed that the GPR model yielded good results compared to the SVM model in rubbercret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Compressive strength predictions for rubberized concrete were made utilizing Gaussian process regression (GPR) models and support vector machine (SVM) by Gregori et al [23]. Previous studies were analyzed for compressive strength data.…”
Section: Crumb Rubbermentioning
confidence: 99%
“…Compressive strength predictions for rubberized concrete were made utilizing Gaussian process regression (GPR) models and support vector machine (SVM) by Gregori et al [23]. Previous studies were analyzed for compressive strength data.…”
Section: Crumb Rubbermentioning
confidence: 99%
“…In recent years, soft computing represented by machine learning (ML) has made remarkable achievements in the prediction of rubber-concrete material performance, e.g., artificial neural networks (ANN) [ 12 , 13 ], support vector machine (SVM) [ 14 , 15 ], back-propagation neural network (BPNN) [ 16 , 17 ], extreme learning machine (ELM) [ 18 , 19 ], multi-layer perceptron (MLP) [ 20 , 21 ] and trees-based models [ 22 , 23 ]. Among the ML models, the random forest (RF) model has an excellent resistance to overfitting and a fitting ability in solving prediction problems [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning has been widely used in classification and prediction by scholars because it can dig out intrinsic relationships from large amounts of historical data for classification or prediction. Such as, deep learning [23,24], random forest (RF) [25], support vector machine (SVM) [26] and backpropagation neural network (BPNN) [27,28], and so on, have been gradually applied to prediction in various engineering fields because of its good accuracy. A comparative study was made by Liu et al [29] on the prediction of frost resistance of recycled concrete by using three methods, including ANN, Gaussian process regression, and multivariate adaptive regression spline; the results showed that, among the three methods, the prediction accuracy of ANN model is the best.…”
Section: Introductionmentioning
confidence: 99%